Health Care Professional-Supported Co-Design of a Mime Therapy-Based Serious Game for Facial Rehabilitation - Daniel Lima Sousa; Silmar Teixeira; José Everton Fontenele; Renato Mendes Santos; Leynilson Pereira; Rodrigo Baluz; Victor Hugo Bastos; Ariel Soares Teles (JMIR Publications, 2024)
This research letter presents the co-design process for RG4Face, a mime therapy-based serious game that uses computer vision for human facial movement recognition and estimation to help health care professionals and patients in the facial rehabilitation process.